Peningkatan kemampuan berhitung melalui permainan congklak modifikasi - Wirdawati Wirdawati; Syahrul Ismet (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
This study aims to determine the improvement of children's numeracy skills through modified congklak games. The type of research used is classroom action research (CAR). The research subjects were 15 students of the Generation of West Pasaman Kindergarten. The time used in this study was 2 months, from July to August 2018. The study was conducted in 2 cycles. Data collection is done by observation and documentation study. Data were analyzed by percentage techniques. The results of the study on the implementation of the first cycle of the first meeting until the third meeting showed an increase in numeracy skills in children. After the second cycle of the first meeting until the third meeting, there was an increase in the numeracy skills of children, especially in counting 1-10, distinguishing the concept of many and few and summing up simply. After being given action on sikulus I and cycle II, it can be concluded that the ability of child counting can be improved by a haughty game of modification.y of child counting can be improved by a haughty game of modification.